Swaddling dan Kangaroo Mother Care Dapat Mempertahankan Suhu Tubuh Bayi Berat Lahir Rendah (BBLR) - Yusnika Damayanti; Titin Sutini; Suhendar Sulaeman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the effect of swaddling and kangaroo mother care on the increase in body temperature of low birth weight infants in Puskesmas Biak Muli, Southeast Aceh. This research is a quasy experimental research design with pre-test and post-test without control. The results of this study obtained the average value of the baby's body temperature before and after swaddling intervention (p value = 0.168, Δ = 0.02) and for the results of interventions before and after KMC obtained values (p value = 0.000, Δ = 0.47 ) and for the results of interventions before and after swaddling + KMC obtained values (p value = 0,000, Δ = 0.58). In conclusion, the combination intervention between swaddling and KMC is more significant compared to swaddling intervention alone and KMC intervention alone. Keywords ; LBW, Kangaroo Mother Care, Body Temperature, Swaddling